Religious Moderation Perspectives On Arabic Language Learning For Islamic Boarding Schools In Lampung - Khotijah, Khotijah; Suhairi, Suhairi; Bin Has, Qois Azizah (Ijaz Arabi Journal of Arabic Learning, 2024)
The study of religious moderation is still a widely discussed topic. The study of religious moderation emerges with moderate values as knowledge that does not contain violence, extremism, and false doctrine,ines of religion in society. However, amid the polemic of extremist ideologies, Islamic boarding schools come with a unique learning system. For example, learning Arabic in Islamic boarding schools can lead students to understand the meaning of moderation in society. The moderate values in the books and the slogans and mottos of the Islamic Boarding School are easily understood and implemented by the students daily. This paper aims to convey and reveal the values of religious moderation in Arabic language learning at Islamic Boarding Schools in Lampung. They are written qualitatively, analyzing several textbooks and slogans in Islamic boarding schools. Based on the results of the analysis of Arabic language learning, the meaning of moderation in Islamic boarding schools that are actively learned by students, such as nationalism, tolerance, tawazun, and fairness, are seen in students' learning and daily activities. The manifestation of moderation values shows that the Islamic Boarding School in Lampung has carried moderate values since its inception and can become an intermediary to maintain societal harmony.